Impact of Human–Elephant Conflict Risk Perception on Farmers’ Land Use Efficiency in Yunnan, China - Mengyuan Zhao; Jia Chen; Beimeng Liu; Yi Xie (Land)
In countries and regions where Asian elephants are distributed, human–elephant conflict has become an important ecological and socio-economic issue. As one of the major habitats of Asian elephants, China faces severe challenges. Based on the theory of planned behavior and the risk perception theory, this study takes the survey data of 449 smallholder farmers in the Asian elephant distribution areas of Pu’er City, Yunnan Province as samples and uses the Tobit model and the mediating effect model to empirically analyze the impact of human–elephant conflict on farmers’ land use efficiency and its mechanism. The results show the following: (1) The human–elephant conflict risk perception has a significant negative impact on farmers’ land use efficiency. A one-unit increase in risk perception decreases land use efficiency by 250.34 CNY/mu. (2) Social networks positively moderate the negative impact of the human–elephant conflict risk perception on farmers’ land use efficiency, further strengthening the negative impact of risk perception. (3) From the perspective of the mechanism, the human–elephant conflict risk perception increases the likelihood of farmers changing their land use behavior. Farmers with high risk perception tend to reduce agricultural capital investment, which in turn leads to a decline in land use efficiency. In view of this, this paper puts forward suggestions in terms of strengthening ecological monitoring and control, increasing support for agricultural production, and guiding rational social network communication, providing theoretical support and practical guidance for alleviating human–elephant conflict and improving farmers’ land resource use efficiency.